Sleep Deprivation Selectively Impairs Interpersonal Trust in Different Social Scenarios: Evidence from the Social Mindfulness Paradigm - Zhu W; Jiang T; Cao Y; Ma N (Nature and Science of Sleep)
Wenwei Zhu,1,2,* Tianxiang Jiang,1,2,* Yixuan Cao,1,2 Ning Ma1,2 1Philosophy and Social Science Laboratory of Reading and Development in Children and Adolescents (South China Normal University), Ministry of Education, South China Normal University, Guangzhou, 510631, People’s Republic of China; 2Center for Sleep Research, Center for Studies of Psychological Application, Guangdong Key Laboratory of Mental Health and Cognitive Science, School of Psychology, South China Normal University, Guangzhou, 510631, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ning Ma, Center for Sleep Research, School of Psychology, South China Normal University, Guangzhou, 510631, People’s Republic of China, Email maning@m.scnu.edu.cnBackground: Sleep deprivation (SD) is widely recognized for its negative impact on both cognitive abilities and social interactions. Nonetheless, the effect of sleep deprivation on interpersonal trust in social scenarios is poorly understood.Purpose: This study investigated the impact of total sleep deprivation on interpersonal trust under two different social scenarios: kindness and unkindness.Patients and Methods: All participants (N = 49) completed the Social Mindfulness paradigm (SoMi) after both normal sleep (NS) and SD. Alertness changes were assessed using the Psychomotor Vigilance test (PVT) and the Karolinska Sleepiness Scale (KSS).Results: Our results demonstrated that SD significantly impaired interpersonal trust when perceiving unkind intentions but did not affect trust in kind intentions (p < 0.05). Additionally, this detrimental effect was not related to changes in alertness (p > 0.05).Conclusion: These findings suggest that SD selectively impacts interpersonal trust, and this effect is not influenced by simple cognitive functions such as alertness. Further research could incorporate brain imaging techniques to explore the association of other cognitive and affective factors with interpersonal trust after sleep loss.Keywords: sleep deprivation, interpersonal trust, intention